2006
DOI: 10.1021/pr0504283
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Analysis of Transcript and Translation Profiles:  Identification of Metastasis-Related Signal Pathways Differentially Regulated by Drug and Genetic Modifications

Abstract: Tumor metastasis is a complex multi-step process normally involving dysregulation of multiple signal transduction pathways. In this study we developed a novel approach to efficiently define dysreguated pathways associated with metastasis by comparing global gene and protein expressions of two distinct metastasis-suppressed models. Consequently, we identified common features shared by the two models which are potentially associated with metastasis.The efficiency of metastasis from the highly aggressive polyoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…This result is consistent with the finding that JAK-mediated activation of STAT1 suppresses metastasis of other types of tumors [24,66]. In contrast, JAK-mediated activation of STAT3 or STAT5 increases metastasis of other tumors [24].…”
Section: Discussionsupporting
confidence: 92%
“…This result is consistent with the finding that JAK-mediated activation of STAT1 suppresses metastasis of other types of tumors [24,66]. In contrast, JAK-mediated activation of STAT3 or STAT5 increases metastasis of other tumors [24].…”
Section: Discussionsupporting
confidence: 92%
“…An additional ICAT study revealed 240 differentially expressed proteins between the metastatic gastric cancer TMC-1 cell line and the noninvasive gastric cancer SC-M1 cell line [60]. Further, when ICAT and microarray gene expression analysis were combined, Stat signal transduction pathways and differential expression of many basement membrane proteins were linked to metastasis inhibition [61]. Taken together, these studies support the application of ICAT to identify differentially expressed proteins related to metastasis.…”
Section: Challenging the Clonal Evolution Model Of Metastasismentioning
confidence: 87%
“…Among many genes involved in the development of metastasis, MSGs are responsible for negative regulation of metastasis by interfering with cancer cell dissemination, tissue invasion, survival, and growth [10,11,[36][37][38][39]. The underlying molecular mechanisms employed by MSGs remain obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there is a dire need for improved prognostic metastatic biomarkers to determine whether primary prostate cancers are potentially aggressive or indolent; in the latter case, patients can be spared from over treatment [9]. www.impactjournals.com/oncotarget Metastasis suppressor genes (MSGs) are negative regulators of metastasis [10,11]. Compelling evidence indicates that modifications of DNA methylation and histones can silence the expression of MSGs, leading to the development of metastasis [12][13][14].…”
Section: Introductionmentioning
confidence: 99%